2021
DOI: 10.1093/jjco/hyab157
|View full text |Cite
|
Sign up to set email alerts
|

Absolute lymphocyte count is an independent predictor of survival in patients with metastatic renal cell carcinoma treated with nivolumab

Abstract: Objective Programmed cell death-1 antibody therapy has demonstrated improved progression-free survival and overall survival in patients with metastatic renal cell carcinoma. However, there are limited studies on biomarkers that can predict the efficacy of immune checkpoint inhibitors. We examined the influence of peripheral inflammatory biomarkers on the clinical outcomes of patients with metastatic renal cell carcinoma treated with nivolumab. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Although white blood cells only account for 0.2% of whole blood, they play an important role in protecting human health [1]. White blood cells are generally divided into neutrophils, eosinophils, basophils, monocytes, and lymphocytes [2], and changes in these cell counts can be used as the basis for diagnosing certain diseases or evaluating the therapeutic efect of certain diseases [3][4][5][6][7][8][9]. Terefore, the accuracy and efciency of white blood cell detection and classifcation are very important for the auxiliary diagnosis of diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although white blood cells only account for 0.2% of whole blood, they play an important role in protecting human health [1]. White blood cells are generally divided into neutrophils, eosinophils, basophils, monocytes, and lymphocytes [2], and changes in these cell counts can be used as the basis for diagnosing certain diseases or evaluating the therapeutic efect of certain diseases [3][4][5][6][7][8][9]. Terefore, the accuracy and efciency of white blood cell detection and classifcation are very important for the auxiliary diagnosis of diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our patients, the rapid increase in absolute lymphocyte counts mainly contributed to the increase in post-PNI values. Elevation of absolute lymphocyte counts after the induction of ICIs has been reported in several cancers, including melanoma, non-small cell lung cancer, and renal cell carcinoma (25)(26)(27)(28)(29). These studies demonstrated that higher absolute lymphocyte counts after the start of ICI (3-6 weeks) led to longer survival.…”
Section: Discussionmentioning
confidence: 81%
“…Karantanous et al reported that lung cancer patients with an ALC ≥1,700/µl have a better OS than for those with <900/µl ( 16 ). Ueda et al demonstrated that the optimal cut-off value of ALC for predicting PFS was 1,300/µl and that an ALC ≥1,300/µl is an independent prognostic factor in metastatic renal cell carcinoma patients ( 28 ). In gastric cancer, Ogata et al ( 18 ) set the cut-off value for NLR in unresectable or recurrent gastric cancer at 5, whereas Yamada et al ( 17 ) set it at 2.5; therefore, the cut-off value differs among studies.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report to predict the outcome and side effects of nivolumab therapy for recurrent esophageal cancer using only blood biochemical examination, such as ACL, NLR, PLR, MLR, and CAR values, or a simple score, PS. As nivolumab therapy for recurrent esophageal cancer is expected to become increasingly widespread, prediction of the prognosis and side effects is essential ( 15 21 , 28 ). The more accurate and predictable a measure is using a simple method, the more frequently it will be used; therefore, ALC and CAR as predictors of the outcome and side effects of nivolumab therapy for recurrent esophageal cancer may be versatile.…”
Section: Discussionmentioning
confidence: 99%